2020
DOI: 10.3390/ijms21218257
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Modulates Macrophage Activation and Contributes Smooth Muscle Cells Apoptosis in Abdominal Aortic Aneurysm Pathogenesis

Abstract: Galectin-3 (Gal-3) is a 26-kDa lectin that regulates many aspects of inflammatory cell behavior. We assessed the hypothesis that increased levels of Gal-3 contribute to abdominal aortic aneurysm (AAA) progression by enhancing monocyte chemoattraction through macrophage activation. We analyzed the plasma levels of Gal-3 in 76 patients with AAA (AAA group) and 97 controls (CTL group) as well as in angiotensin II (Ang-II)-infused ApoE knockout mice. Additionally, conditioned media (CM) were used to polarize THP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…In patients with altered renal function, increased plasma levels of galectin-3 have been associated with higher risk of renal function decline, incident chronic kidney disease, and renal failure [ 52 ]. Galectin-3 is involved in many processes during acute inflammatory responses, including neutrophil activation and adhesion and chemoattraction of macrophages [ 56 , 57 ]. Lu HY et al demonstrated that galectin-3 is responsible for macrophage activation by inducing monocyte-macrophage differentiation and amplifying inflammation [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with altered renal function, increased plasma levels of galectin-3 have been associated with higher risk of renal function decline, incident chronic kidney disease, and renal failure [ 52 ]. Galectin-3 is involved in many processes during acute inflammatory responses, including neutrophil activation and adhesion and chemoattraction of macrophages [ 56 , 57 ]. Lu HY et al demonstrated that galectin-3 is responsible for macrophage activation by inducing monocyte-macrophage differentiation and amplifying inflammation [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 is involved in many processes during acute inflammatory responses, including neutrophil activation and adhesion and chemoattraction of macrophages [ 56 , 57 ]. Lu HY et al demonstrated that galectin-3 is responsible for macrophage activation by inducing monocyte-macrophage differentiation and amplifying inflammation [ 56 ]. Moreover, several studies have postulated that macrophages are the major source of galectin-3 driving renal fibrosis through myofibroblast activation [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…46,47 The activated inflammatory macrophages may up-regulate the expression of Fas protein in VSMC via TNF-α and IL-1β, promote VSMC apoptosis, and the proliferation ability of VSMC was also influenced by macrophages, which regulated the formation of intima. 48,49 Through single cell sequencing, it was found that the receptor-ligand interaction between VSMC and immune cell population in aortic dissection was significantly up-regulated, especially for macrophages and T cells. Therefore, compared with single cells such as macrophages or VSMCs, the interaction between two or even more types of cells played a more significant role in the process of vascular remodeling in aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
“…There exist two activated states of macrophages, characterized by a pro-inflammatory classical activation phenotype (M1) and an anti-inflammatory alternative activation phenotype (M2) [82]. Blocking the expression of Gal3 reduced the expression of IL-8, TNF-α, and IL-1β in M1 macrophages [83]. Moreover, Gal3 takes part in the polarization of the M2 subtype, while M2 macrophages could upregulate the secretion of Gal3 in return.…”
Section: Gal3 and Macrophagementioning
confidence: 99%